White House years - Kissinger, Henry, 1923-2023. (Canada Little, Brown & Company, 1979)
"Dr. Kissinger recalls ... his first meeting with Nixon, his secret trip to China, the first SALT negotiation, the Jordan crisis of 1970, the India-Pakistan war of 1971 ... the historic summit meetings in Peking and Moscow ... events in Laos, the overthrow of Cambodia's Prince Sihanouk, his secret talks with the North Vietnamese in Paris, his "peace is at hand" news conference ... the Christmas bombing of 1972 ... Middle East conflicts, Sadat's break with the Soviets, the election of Salvador Allende in Chile, issues of defense strategy, and relations with Europe and Japan."
Originally published: Boston : Little, Brown, c1979.
"The first volume of his classic memoirs"--Cover.
Includes bibliographical references and index.
Keywords: Nixon, Richard M. -- 1913-1994.; Kissinger, Henry, -- 1923-2023.; Statesmen -- United States -- Biography; United States -- Foreign relations -- 1969-1974.; Biographies